If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -1) + 16 = 8x + 1 Reorder the terms: 5(-1 + 2x) + 16 = 8x + 1 (-1 * 5 + 2x * 5) + 16 = 8x + 1 (-5 + 10x) + 16 = 8x + 1 Reorder the terms: -5 + 16 + 10x = 8x + 1 Combine like terms: -5 + 16 = 11 11 + 10x = 8x + 1 Reorder the terms: 11 + 10x = 1 + 8x Solving 11 + 10x = 1 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 11 + 10x + -8x = 1 + 8x + -8x Combine like terms: 10x + -8x = 2x 11 + 2x = 1 + 8x + -8x Combine like terms: 8x + -8x = 0 11 + 2x = 1 + 0 11 + 2x = 1 Add '-11' to each side of the equation. 11 + -11 + 2x = 1 + -11 Combine like terms: 11 + -11 = 0 0 + 2x = 1 + -11 2x = 1 + -11 Combine like terms: 1 + -11 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 3x+1=2x-1 | | -24=6a-15-15a | | 10-10x=75-45x | | 5x-4=-4+5x | | x^4-x^3+1=0 | | 5x=4(x+3) | | 5a-9=26 | | 1=14(2r+1) | | 14-6x=2x+66 | | 8x+29x-6= | | 1.4m-06(m-2)=2.4m | | 2x+40=12x-40 | | 5x-4=2x+6+x | | 37x=9x+4 | | 2(x-7)=10-4x | | 25x^2-15x-4=0 | | 12-6x=6x+34 | | 6x-10=46 | | 2+5+6rs= | | 2(y-6)-(y+2)=26 | | (x^2+16)(x^3-108)=0 | | 14a+12=84 | | 9[(4+4)-2]= | | .1(x^2+16)(x^3-108)=0 | | 4=5-3x | | -5(t-4)-7= | | 17=-5x-13 | | 6x+1=4x-3 | | 14=18-4x | | 1/9(p+18)+1/3(2p+3)=p+3 | | 2=-x-5 | | 13q-13q=22 |